2
$\begingroup$

Integrate $$\int \frac{\mathrm dx}{(x-2)(\sqrt{x^2-4x+3})}$$

$$\int \frac{\mathrm dx}{(x-2)(\sqrt{x^2-4x+3})}=\int \frac{\mathrm dx}{(x-2)(\sqrt{(x-2)^2-(1)^2})}=\operatorname{arcsec}(x-2)+\rm C$$

Wolfram writes that the answer is $-\arctan\left(\frac{1}{\sqrt{x^2-4x+3}}\right)+\rm C\;.$

$\endgroup$
1
$\begingroup$

if you draw a right angled triangle you can see that $\operatorname{arcsec}(x-2)$ is equivalent to $\arctan\sqrt{x^2-4x+3}$ which in turn is equivalent to $\frac{\pi}{2}-\arctan\frac{1}{\sqrt{x^2-4x+3}}$, so the answers are the same give or take a constant

$\endgroup$
2
$\begingroup$

$$\begin{align} \int\frac{\mathrm{d}x}{\left(x-2\right)\sqrt{x^{2}-4x+3}} &=\int\frac{\mathrm{d}x}{\left(x-2\right)\sqrt{\left(x-1\right)\left(x-3\right)}}\\ &=\int\frac{\mathrm{d}t}{t\sqrt{t^{2}-1}};~~~\small{\left[x=t+2\right]}\\ &=\int\frac{1}{t^{2}}\cdot\frac{t\,\mathrm{d}t}{\sqrt{t^{2}-1}}\\ &=\int\frac{\mathrm{d}u}{1+u^{2}};~~~\small{\left[\sqrt{t^{2}-1}=u\right]}\\ &=-\int\frac{\left(-u^{-2}\right)\,\mathrm{d}u}{u^{-2}+1}\\ &=-\int\frac{\mathrm{d}w}{w^{2}+1};~~~\small{\left[u^{-1}=w\right]}\\ &=-\arctan{\left(w\right)}+\color{grey}{constant}\\ &=-\arctan{\left(\frac{1}{u}\right)}+\color{grey}{constant}\\ &=-\arctan{\left(\frac{1}{\sqrt{t^{2}-1}}\right)}+\color{grey}{constant}\\ &=-\arctan{\left(\frac{1}{\sqrt{\left(x-2\right)^{2}-1}}\right)}+\color{grey}{constant}.\blacksquare\\ \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.